EFEKTIVITAS PROMOSI KESEHATAN DALAM PENGELOLAAN SAMPAH DI KAWASAN WISATA MANDALIKA: TANTANGAN DAN STRATEGI MENUJU PARIWISATA BERKELANJUTAN - Dewi Utary (Yayasan Nusantara Hasana Berdikari, 2025)
The Mandalika tourism area has experienced a 25% annual increase in visitor numbers since 2019, generating more than 30 tons of waste per month, with the majority consisting of plastic waste (60%) and organic waste (25%). This study aims to analyze the effectiveness of health promotion in waste management in Mandalika. The methods used include surveys and interviews with 200 respondents, consisting of tourists, local communities, and tourism operators. Survey results indicate that 70% of tourists are aware of the importance of disposing of waste properly, but only 45% consistently practice it. Among the local community, 85% support cleanliness programs, but only 50% understand proper waste management, including the separation of organic and inorganic waste. Health promotion interventions conducted through posters, social media, and education in local schools have increased awareness by 30% among the community and visitors. This study found limitations in waste bin facilities, which cover only 60% of public areas, as well as a lack of training for tourism operators on the importance of cleanliness. The study recommends enhancing health promotion programs by expanding cleanliness campaigns, providing waste management facilities throughout tourist areas, and empowering local communities as environmental ambassadors. Collaborative efforts between the government, the community, and tourists are expected to create a cleaner and more sustainable tourism environment.